Pengaruh Kemandirian Belajar terhadap Pemecahan Masalah Matematis Siswa Kelas X SMK Dewantara Cibinong - Roida Eva Flora Siagian; Novi Marliani; Dyska Printia Aqisna (Departement of Mathematics Education, 2022)
There are several factors that contribute to low independence in learning, one of which is the ability of the students themselves. This study aimed to find out how independent learning affects students' ability to solve mathematical problems. The study's population was made up of 36 class X students at SMK Dewantara Cibinong. The students were observed in order to gather data for the study. This study uses a qualitative descriptive approach to examine the correlation between two variables. The study aimed to find out whether there is a link between being able to learn independently and being good at solving mathematical problems relating to two-variable linear programming. The study used a self-learning questionnaire and a test of mathematical problem-solving abilities to collect data. The data analysis used in this study included a product moment correlation analysis to measure the relationship between independent learning and mathematical problem solving abilities. The results of this study suggest that independent learning does not have a significant impact on solving math problems for class X students of SMK Dewantara Cibinong. However, it is possible that the data collected was not sufficient to prove a relationship between independent learning and math problem solving.